Hygrothermal aging and structural damage of a jute/poly (lactic acid) (PLA) composite observed by X-ray tomography. (22nd March 2019) - Jiang, Ning; Yu, Tao; Li, Yan; Pirzada, Talha J.; Marrow, Thomas James
Abstract: Biodegradable plant fiber reinforced poly (lactic acid) (PLA) composites are potential replacements for traditional synthetic fiber reinforced composites. These may experience hygrothermal aging from the combined effects of moisture and heat. The effects of aging in water at 50 °C on water absorption, chemical degradation of the fibers and matrix, and the tensile properties of a jute fiber/PLA composite have been correlated with changes in the internal structure, observed by high-resolution computed X-ray tomography. Water absorption during aging causes fiber/matrix interface failure and then matrix embrittlement, and these are detrimental to the tensile strength, stiffness and ductility.